Sosialisasi Dan Pelatihan Kesehatan Ruminansia Kepada Kelompok Ternak Kopi Manis Desa Papar Kecamatan Papar Kabupaten Kediri - Tanjungsari, Ardina; Andaruisworo, Sapta; Yuniati, Erna; Anifiatiningrum (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this activity is to provide socialization and training on ruminant livestock health to the Kopi Manis Livestock Group in Papar Village, Papar District, Kediri Regency. It is expected that after the socialization and training on livestock health, all members of the Kopi Manis Livestock Group will increase their insight, knowledge, and actions to handle cases of disease in ruminant livestock. This community service activity was carried out using the Participatory Rural Approach (PRA) method, which is a method of educating knowledge and insight to the community or community groups through training, practice, and mentoring. In this PRA method, it was chosen because this PRA method has advantages including the active involvement of community members or groups, in this case the Kopi Manis Livestock Group as the subject. In this socialization and training activity, it was filled with an explanation of various ways to handle ruminant livestock health and how to prevent and treat the types of diseases that usually attack ruminant livestock. As we know, cases of FMD (Foot and Mouth Disease) have caused many problems and great losses for livestock farmers. Also included in this case, when the FMD case broke out, many cattle and goat farmers in the Papar Village area, Papar District, Kediri Regency, experienced paralysis and death in their livestock. Such conditions are certainly very detrimental to farmers. In response to the conditions and problems after the FMD case in Papar Village, Papar District, Kediri Regency, a solution is needed to anticipate the occurrence of FMD cases not recurring or spreading again in the Papar area, so socialization and training are needed on disease prevention and health care for ruminant livestock. It is hoped that with the socialization and training on livestock health, it can provide provisions and knowledge for farmers who are especially members of the Sweet Coffee Livestock Group.